COMPLEXO HIPERPLASIA ENDOMETRIAL CÍSTICA (PIOMETRA) EM CADELAS – DIAGNÓSTICO E TERAPÊUTICA - Augusto Schweigert; Aline Aparecida Silva; Urias José correa Neto; Cassia Maria Barroso Orlandi; Sabrina Marin Rodigheri (Colloquium Agrariae, 2009)
Cystic endometrial hyperplasia-pyometra complex is a disease that affects a large number of bitches. It has high morbity and mortality routes, and it occurs particularly in middle-aged bitches during diestrus phase. The bitches with pyometra exhibit apathy, anorexia and possible signs of acute renal failure due to renal parenchyma injuries. There are two types of pyometra: open and closed. The most common sign of open pyometra is the purulent vaginal discharge. In closed pyometra, diagnostic is facilitated by abdominal palpation, laboratory test, ultrasound and X-ray. If untreated, pyometra can cause renal failure, sepsis, septic shock and death. Treatment of pyometra is based on medical or surgical procedures. The treatment choice may vary according to the clinical signs and the state of the patient.